2008
DOI: 10.1016/j.visres.2008.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of smooth-pursuit eye movements by real and illusory contours

Abstract: It is well established that elementary motion detectors are only able to code for the movement of a contour perpendicular to its orientation. This shortcoming explains why the initial direction of smooth-pursuit eye movements is directed orthogonal to the orientation of a moving contour independent of its veridical direction of motion. Here, we replicated this finding and asked whether this directional error can be reduced by subjects' prediction of upcoming target moving direction and whether this directional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Psychophysical studies that directly investigated the effect of eccentricity on sensitivity to texture pop-out found that detection was optimal in the periphery (Fiorentini, 1989; Meinecke, 1989). Related to this, an eye-tracking study by Biber and Ilg (2008) found that pursuit initiation to illusory contour stimuli occurs before contour completion can take place, suggesting that segmentation facilitates fixation upon a salient region and that the perception of a figure’s contours requires the high spatial precision afforded by central viewing (Hirsch & Curcio, 1989).…”
Section: Introductionmentioning
confidence: 91%
“…Psychophysical studies that directly investigated the effect of eccentricity on sensitivity to texture pop-out found that detection was optimal in the periphery (Fiorentini, 1989; Meinecke, 1989). Related to this, an eye-tracking study by Biber and Ilg (2008) found that pursuit initiation to illusory contour stimuli occurs before contour completion can take place, suggesting that segmentation facilitates fixation upon a salient region and that the perception of a figure’s contours requires the high spatial precision afforded by central viewing (Hirsch & Curcio, 1989).…”
Section: Introductionmentioning
confidence: 91%
“…Translating Bars In [20,8] the authors consider tilted translating bars. Pursuing a translating bar which true motion direction is not normal to its orientation leads to initial deviation in the smooth pursuit eye movement direction.…”
Section: Line-drawing Objectsmentioning
confidence: 99%
“…• [8]. To obtain a model evaluation procedure, the slope of the directional errors could be analysed with respect to bar length, number of bar tiles.…”
Section: Line-drawing Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some debate over the years whether pursuit correlates better with physical or perceived stimulus motion. When physical and perceived motions are different, the oculomotor system mostly follows the percept rather than the physical stimulus (Beutter & Stone, 1998Biber & Ilg, 2008;Hafed & Krauzlis, 2006Ilg & Thier, 2003;Madelain & Krauzlis, 2003;Ringach, Hawken, & Shapley, 1996;Steinbach, 1976;Wyatt, Pola, Fortune, & Posner, 1994). One particularly interesting case of perceived motion is the illusory motion caused by the motion aftereffect (MAE) in which there is no physical motion at all.…”
Section: Illusory Motionmentioning
confidence: 99%